CLIMATE-RESILIENT HYDRAULIC INFRASTRUCTURE: STRATEGIES FOR FLOOD CONTROL AND WATER RESOURCE MANAGEMENT IN ARID REGIONS - Sh. Egamberdiyeva (Modern American Journals, 2025)
This article presents a comprehensive scientific study of climate-resilient hydraulic infrastructure and its strategic role in mitigating flood risks and ensuring sustainable water resource management in arid regions. As global climate change accelerates, arid and semi-arid zones face increasing extremes of hydrological variability—characterized by prolonged droughts and sudden, intense floods—posing new challenges to traditional hydraulic systems. The research synthesizes theoretical approaches, engineering practices, and real-world case studies, particularly focusing on Central Asia and Uzbekistan. Through an integrative methodology combining climatic modeling, hydraulic simulations, and policy evaluation, the study explores how hybrid infrastructure—merging grey and green engineering—can enhance resilience, improve water retention, and reduce vulnerability to climate-induced water stress. The findings emphasize the need for adaptive planning, ecosystem-based design, and cross-sectoral governance. The article concludes with practical recommendations to guide engineers, planners, and policymakers toward implementing infrastructure systems that are robust, flexible, and sustainable in the face of a rapidly changing climate.
Keywords: Climate-resilient infrastructure, hydraulic engineering, arid regions, flood control, water resource management, adaptive design, sustainability.